2020
DOI: 10.2337/dc20-0352
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Age of Onset of Type 2 Diabetes and the Long-term Risk of End-Stage Kidney Disease: A National Registry Study

Abstract: The long-term risk of end-stage kidney disease (ESKD) in type 2 diabetes is poorly described, as is the effect that younger age of diabetes onset has on this risk. Therefore, we aimed to estimate the effect of age of onset on the cumulative incidence of ESKD from onset of type 2 diabetes. RESEARCH DESIGN AND METHODSThis study included 1,113,201 people with type 2 diabetes registered on the Australian National Diabetes Services Scheme (NDSS) followed from 2002 until 2013. The NDSS was linked to the Australia an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 30 publications
3
41
0
1
Order By: Relevance
“…Recent studies also demonstrated a higher risk of microvascular complications such as progressive chronic kidney disease [6] and retinopathy [24] in individuals with early-onset T2DM. However, studies have suggested that patients with early-onset T2DM were at increased risk of cardio-renal complications mainly driven by longer diabetes duration [4,7,10,25] . A recent study from Australia found that diabetes duration was the predominant determinant of end-stage kidney disease (ESKD) and the incidence of ESKD was higher at a given duration in those diagnosed later, which may be partly related to the increased risk at an advancing age [10] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies also demonstrated a higher risk of microvascular complications such as progressive chronic kidney disease [6] and retinopathy [24] in individuals with early-onset T2DM. However, studies have suggested that patients with early-onset T2DM were at increased risk of cardio-renal complications mainly driven by longer diabetes duration [4,7,10,25] . A recent study from Australia found that diabetes duration was the predominant determinant of end-stage kidney disease (ESKD) and the incidence of ESKD was higher at a given duration in those diagnosed later, which may be partly related to the increased risk at an advancing age [10] .…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have suggested that patients with early-onset T2DM were at increased risk of cardio-renal complications mainly driven by longer diabetes duration [4,7,10,25] . A recent study from Australia found that diabetes duration was the predominant determinant of end-stage kidney disease (ESKD) and the incidence of ESKD was higher at a given duration in those diagnosed later, which may be partly related to the increased risk at an advancing age [10] . Because the actual age, age at diagnosis, and duration of diabetes are all important risk factors for diabetes complications such as chronic kidney disease and ESKD [20,26] , an appropriately designed study which takes into full consideration the confounding or impact from the actual age and diabetes duration is needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To estimate the ESKD incidence and all-cause mortality rates used for estimation of the lifetime risk of ESKD and projections of the incidence of ESKD-D, we used data derived from linkage of the National Diabetes Services Scheme (NDSS) to the Australia and New Zealand Dialysis and Transplant Registry (ANZDATA) and the Australian National Death Index (NDI) for 2002-2013, as previously described (1). Briefly, the NDSS was established by the Australian government in 1987 and includes 80-90% of people with diagnosed diabetes in Australia.…”
Section: Supplementary Text 1 -Description Of Data Sources For Model Inputs and Uncertainty In Model Parametersmentioning
confidence: 99%
“…Incidence of ESKD and mortality rates among people without ESKD as a function of sex, age and duration of diabetes were predicted in order to estimate the lifetime risk of ESKD, as well as project the incidence of ESKD, using a framework previously described (1). Briefly, National Diabetes Services Scheme registrants were followed from 1 January 2002 or date of registration, if later, until onset of ESKD, death, or end of follow-up on 31 December 2013.…”
Section: Supplementary Text 2 -Estimation Of Sex Age and Duration-specific Eskd Incidence And All-cause Mortality Ratesmentioning
confidence: 99%